2019
DOI: 10.3748/wjg.v25.i32.4614
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional treatments for hepatocellular carcinoma: Current evidence and future directions

Abstract: Liver cancers are the second most frequent cause of global cancer-related mortality of which 90% are attributable to hepatocellular carcinoma (HCC). Despite the advent of screening programmes for patients with known risk factors, a substantial number of patients are ineligible for curative surgery at presentation with limited outcomes achievable with systemic chemotherapy/external radiotherapy. This has led to the advent of numerous minimally invasive options including but not limited to trans-arterial chemoem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 113 publications
(114 reference statements)
0
73
0
Order By: Relevance
“…Finally, if the initial decision in this patient is to pursue TACE, there is emerging evidence from several Asian centers that combination therapy with TACE followed by RFA in BCLC A and B patients with HCC larger than 3 cm is generally safe and leads to superior overall and progression-free survival compared with TACE alone. (86)(87)(88)(89)(90)(91)(92) Chu et al (91) showed improved outcomes in patients undergoing combination TACE-RFA for a single 3.1-5 cm HCC compared with either modality alone. In a recent single-center retrospective analysis of 128 patients undergoing TACE-RFA compared with 271 receiving TACE alone, Ren et al (87) found improved overall and progression-free survival at 5 years, not only for patients with tumor diameter of 3.1-5 cm, but also for those with tumors larger than 5 cm as well.…”
Section: Choosing Among Lrt Optionsmentioning
confidence: 99%
“…Finally, if the initial decision in this patient is to pursue TACE, there is emerging evidence from several Asian centers that combination therapy with TACE followed by RFA in BCLC A and B patients with HCC larger than 3 cm is generally safe and leads to superior overall and progression-free survival compared with TACE alone. (86)(87)(88)(89)(90)(91)(92) Chu et al (91) showed improved outcomes in patients undergoing combination TACE-RFA for a single 3.1-5 cm HCC compared with either modality alone. In a recent single-center retrospective analysis of 128 patients undergoing TACE-RFA compared with 271 receiving TACE alone, Ren et al (87) found improved overall and progression-free survival at 5 years, not only for patients with tumor diameter of 3.1-5 cm, but also for those with tumors larger than 5 cm as well.…”
Section: Choosing Among Lrt Optionsmentioning
confidence: 99%
“…Men are confronted with approximately threefold higher risk than women, on account of higher likelihood to smoking and drinking (El-Serag and Kanwal, 2014). Main risk factors of HCC are closely related to hepatitis B virus (HBV), hepatitis C virus (HCV), alcoholic liver disease (ALD), NAFLD, liver fibrosis, obesity, diabetes, and smoking (Inchingolo et al, 2019). Most cases of HCC are detected at advanced stages and less than 40% of HCC patients have the chance to be treated surgically (Forner et al, 2012).…”
Section: Nlrp3 Inflammasome and Hcc Hepatocellular Carcinomamentioning
confidence: 99%
“…The majority of patients present with multiple tumors or portal vein tumor invasion are treated with transarterial chemoembolization (TACE), and recent guidelines recommend TACE for those selected patients as a rst-line treatment [4,5]. TACE, which selectively obstructs the tumor vessels, is conventionally performed by intra-arterial infusion of lipiodol or microspheres, along with chemotherapeutics [6]. However, as patients with advanced HCC treated by TACE vary tremendously in prognosis, the most valuable treatment modality of TACE deserves exploring [7,8].…”
Section: Introductionmentioning
confidence: 99%